University Narratives on Latin American Culture and Identity: Critical Discourse Analysis in Educational Media (Islas, 2026)
Introduction: Higher education and educational media play a central role in the construction of university culture and identity in Latin America, influencing perceptions of diversity, social inclusion, and the preservation of local traditions. This study analyzes how Latin American universities communicate their culture and identity through their educational media, providing relevant insights for researchers, teachers, and intercultural communication managers, as well as for the design of inclusive educational policies.Methods: A qualitative documentary study was conducted through the systematic review of institutional websites, newsletters, and official communications from 30 Latin American universities, totaling 120 documents. Critical discourse analysis was applied to identify patterns of representation, narrative strategies, and meaning constructions, as well as possible cultural stereotypes.Results: The results reveal recurring patterns related to cultural diversity, institutional identity, representation of local traditions, and the promotion of the university image. Approximately 75 % of the texts emphasize institutional values and visibility strategies.Conclusions: It is concluded that university educational media act as agents of cultural construction and mediators of identity, making diversity visible and reinforcing institutional identity in the region. Strengthening inclusive and culturally sensitive communication is recommended in order to support intercultural educational policies, foster critical citizenship, and promote equity in higher education. The findings broaden the understanding of how Latin American universities construct and communicate their cultural identities from a multidimensional humanistic perspective.
Keywords: educational media; cultural diversity; Latin American universities; institutional identity; critical discourse analysis